A matemática do resto: aplicações de congruência para as séries finais do Ensino Fundamental e Médio - Paiva, Gilberto de (2016)
This work consists of activities proposed for use in elementary and secondary education, addressing Integers, Linear Diophantine Equations, congruence and its applications, such as Chinese Remainder Theorem and organizing a schedule. Each chapter contains a theoretical development contextualized, exercises and their solutions.